SIKULUJIYYA AL-MU’ALLIF FI QASHIDAH AN-NAHDLIYYAH LI MUHAMMAD FAISOL FATAWI ‘ALA NADHARIYYAH ALLPORT - Ummi Hasanah; Betty Ayunda Wulandari; Muhamad Husain Rifa’i; Nehemiah Michael Akia (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2026)
This study examines the psychological profile of M. Faisol Fatawi, the author of Qasidah An-Nahdliyyah, using Gordon Allport’s personality theory, with a particular focus on how psychological dimensions are reflected in literary production. Employing a descriptive qualitative method, this research analyzes narrative data through the framework of traits, habits, and attitudes. The findings reveal that the author’s dominant traits consistency, diligence, and social awareness are systematically manifested in his writing practices and thematic choices. His habits of drawing inspiration from meaningful moments and maintaining humility, along with his reflective and service-oriented attitudes, significantly shape the construction of the text. This study offers a novel contribution by demonstrating the integration of Allport’s psychological framework into the analysis of contemporary Islamic literary works, highlighting how individual personality structures can function as a driving force in ideological and cultural expression. The Qasidah An-Nahdliyyah thus emerges not only as a literary product but also as a medium for articulating the author’s devotion to Nahdlatul Ulama and his intention to inspire broader social engagement.